BIOCHEMICAL PROPERTIES OF RECOMBINANT ALKALINE PHOSPHATASE FROM BACILLUS LICHENIFORMIS T5 - Kirillov , S.O.; Khassenov , B.B.; Silayev , D.V. (Eurasian Journal of Applied Biotechnology, 2017)
In this work, recombinant alkaline phosphatase (phoB) from Bacillus licheniformis was successfully expressed in Escherichia coli, purified and biochemically characterized. Gene coding alkaline phosphatase was amplified from genomic DNA of B. licheniformis and cloned into expression vector pET-28c (+). Using the recombinant vector, a BL21 (DE3)/pAlPh strain-producer was obtained with over expression of the gene. Optimal cultivation parameters for producing recombinant alkaline phosphatase have been determined; 10 mg of protein was purified from 1 liter of culture. The activity of the recombinant alkaline phosphatase is 100 U/mg at standard conditions. Biochemical characteristics of recombinant alkaline phosphatase showed that enzyme has maximum activity at pH=10.0 and temperature +60°C. The kinetics of p-nitrophenyl phosphate hydrolysis have been studied, the Michaelis constant Km was 0.91±0.13 mM and the limiting value of the maximal rate of the enzymatic reaction Vmax was 21.4±1.19 mM. Experiments were carried out to determine the dependence of the enzyme activity on various divalent metals.